Feminist Security Studies and Care Ethics: Security in Latin America in the Wake of the Pandemic - Leone, Mariana S.; Caballero, Sergio (FLACSO - Sede Ecuador, 2021)
Security in Latin America has traditionally been addressed from a state-centric and notable realistic perspective, underlining the threats to the state, from an external actor or from internal destabilization. This paper aims to highlight the suitability of incorporating Feminist Security Studies and Care Ethics in security analysis in order to redefine threats and what “feeling safe” implies, especially in the scenario generated by the COVID-19 pandemic. To this end, the gaps and silences in mainstream theories in the diagnoses on the worsening of the security challenges in the first semester of the pandemic are evidenced. Also, the nuances and perceptions of security included in the Care Ethics approach are highlighted. It is concluded that the conceptual broadening that the Care Ethics approach entails is relevant to analyze —academically and politically— the security threats in Latin America.